What to do next? A common problem amongst researchers - Pestana, M. H. (2018)
The body of relevant literature in the digital information age is growing rapidly. Detecting the signs of potential valuable ideas has theoretical and practical benefits which can help one understand when, how and why a research issue has potential value in the scientific domain. The perceived value of this paper is to show the contribution of a scientometric analysis for an up-to date understanding of the scientific field’s intellectual structure and identify exactly how a current issue connects with previously disparate patches of knowledge, creating a network of ideas cognitively demanding. Applying a multiple temporal, structural and semantic metrics, scientometric analysis allows the visualization of patterns from both citing and cited items. The temporal interval is sliced into equal mutually exclusive time periods, and an individual citation network is derived from each slice. Networks of keywords, authors, categories, sources of publication are included for a better understanding of the subject of the scientific domain. This analysis allows the identification of trends and areas of research conducted so far, and an appreciation of the most relevant authors, papers, sources of publication, showing where most of the studies have been performed. This is pertinent if the trust of future research is to incorporate more innovative approaches. By building on prior research this creates a strong theoretical background, which is an issue in various areas of research, namely, tourism and marketing. Executives who continue to attempt to navigate with out-of-date strategies will be ill-prepared to avail themselves of the immense opportunities. Scientometrics provides a reflexive marking of research into any knowledge domain.